ALLERGY AND ANTIHISTAMINIC MEDICATIONS - R.M. Torshkhoeva (Union of pediatricians of Russia, 2008)
The article reviews the urgent issue of the allergology, which is the application of the antihistaminic medications. The author has demonstrated the advantages of the 2nd generation medications, which have a selective impact on the H1 receptors and do not cause any sedative or anticholinergic effects. She also showed high efficiency of cetirizine, a representative of the given group, for the treatment of the all year round rhinitis and other allergies.Key words: allergies, pathogenesis, treatment, Н1 receptor blockers, children.